UPAYA PEMBERDAYAAN WALIMURID DALAM MENINGKATKAN HASIL TAHFIDZ AL-QURAN - Nafi'ah, Siti; Sembodo, Sigit Priyo; Rokhman, Mauhibur (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This article aims to describe the efforts to empower parents in improving the results of tahfidz Al-Quran and at the Raudlatul Athfal Islamiyah institution in Ngasem Bojonegoro. This article uses qualitative research with a case study approach. Data collection techniques with interviews, observation and documentation. The results of this study are: 1. Efforts to empower students' parents to improve the results of tahfidz al-quran and hadith at the Raudlatul Athfal Islamiyah Ngasem Bojonegoro institution occur through increasing parental awareness of their role as guardians of students in order to shape personalities towards the goodness and happiness of students. The empowerment of guardians of students is triggered by the effectiveness and efficiency of the implementation of the Yahqi method which focuses on the involvement of guardians of students in addition to the use of tone and movement in memorizing short letters of the Koran and short hadiths. 2. Obstacles and obstacles that accompany the empowerment of guardians in improving the results of tahfidz al-quran and hadith at the Raudlatul Athfal Ngasem Bojonegoro institution consist of obstacles to the guardians of students, obstacles to managerial aspects and obstacles to psychological technical aspects.